Knowledge, attitude, and misconceptions of public regarding vitiligo - Fawwaz Freih Alshammrie; Ibrahim G Al Reshidi; Maram O Al Rashidy; Salwa M Al Anazi (Wolters Kluwer Medknow Publications, 2019)
Background: Previous studies of vitiligo have discussed attitudes of vitiligo patients toward their disease. However, few studies have addressed this issue from the public's point of view. Objectives: The main objective is to explore the knowledge, perceptions, misconceptions, and attitudes of the public toward vitiligo. Subjects and Methods: This cross-sectional survey was done using a self-constructed questionnaire. Participants were recruited from the students and employees of Hail University from April 1, 2015 to the end of November 2015. The data were collected and analyzed using Statistical Package for the Social Sciences (SPSS release 20.0). P < 0.05 was accepted for statistical significance. Results: The study included 1004 participants; 440 (43.8%) were male and 564 (56.2%) were female. 231 participants (23%) had no information about vitiligo (P = 0.011). 90.2% of the participants reported that available sources of information about the disease in general are not enough. The main source of information for males and females was the internet. Majority of surveyed participants believed that vitiligo is an inherited disease (59%). Conclusion: The misconceptions and negative attitudes about vitiligo among public are generally prevalent. Educating the public about vitiligo could lead to increased self-confidence, psychological well-being, and resulting in better adaptation of vitiligo patients in the society.